POSTWAR JAPANESE ADOPTION OF AMERICAN CULTURE IN LYNNE KUTSUKAKE’S THE TRANSLATION OF LOVE: A POSTCOLONIAL APPROACH - Bhakti Satrio Nugroho; Muh. Arif Rokhman (Rubikon : Journal of Transnational American Studies, 2019)
This paper discusses postwar Japanese adoption of American culture in a debut novel by Lynne Kutsukake entitled The Translation of Love. This novel is set during the U.S. occupation of Japan after the end of World War II. Postwar Japanese are forced to live under American power, while undergoing an economic, social, and moral crisis (kyodatsu). By using postcolonial perspective under Transnational American Studies, this paper finds the adoption of American culture by postwar Japanese characters in the novel, which come from various social backgrounds, including schoolteachers, schoolchildren, bar girls, and prostitutes. The adoption of American culture includes language (English), Western dating (lifestyle), custom, and fashion. This cultural adoption can be defined as the construction of new Japanese society built under American influence to be more “American-oriented”. Moreover, it further implies the devaluation of Japanese culture, the humiliation of postwar Japanese people, and the birth of Japanese cultural dependency toward American culture.Keywords: American culture; postcolonial; postwar Japan; transnational; U.S. occupation